Numerical Solution of Singularly Perturbed Differential-Difference Equations using Multiple Fitting Factors - Adilaxmi, M.; Bhargavi, D.; Phaneendra, K. (Communications in Mathematics and Applications, 2019)
In this paper, a numerical scheme is proposed to solve singularly perturbed differentialdifference equations with boundary layer behaviour using two fitting factor inserted at convective and diffusion terms. The singularly perturbed differential difference equation is replaced by an equivalent two point singularly perturbation problem. Then to handle the boundary layer, a two parameter fitted scheme is derived and it is applied to get the accurate solution. Model examples are solved using this approach and numerical results along with graphical representation are shown to support the method.